DCIS in BRCA1 and BRCA2 mutation carriers: prevalence, phenotype, and expression of oncodrivers C-MET and HER3. Issue 1 (December 2015) - Yang, Rachel; Mick, Rosemarie; Lee, Kathreen; Graves, Holly; Nathanson, Katherine; Domchek, Susan; Kelz, Rachel; Zhang, Paul; Czerniecki, Brian
Abstract Background Studies report conflicting evidence regarding the existence of a DCIS-associated premalignant pathway in BRCA mutation carriers. We aimed to examine the prevalence, phenotype, and expression of oncodrivers in pure DCIS (pDCIS) and invasive breast cancer with concurrent DCIS (IBC + DCIS) in mutation carriers. Methods A cohort of BRCA1 and BRCA2 mutation carriers >18 years old who underwent surgery for breast cancer at an academic hospital (1992–2011) and had pathology available for review were included for study. Invasive breast cancer (IBC) and DCIS were stained for ER, PR, HER1, HER2, and HER3, and C-MET. DCIS prevalence was evaluated. Correlation of IBC and DCIS phenotypes was evaluated in patients with IBC + DCIS. DCIS and IBC expression of tumor markers were examined by BRCA mutation. Results We identified 114 breast tumors. Of all BRCA1-associated tumors, 21.1 % were pDCIS and 63.4 % were IBC + DCIS. Of all BRCA2-associated tumors, 23.3 % were pDCIS and 60.5 % were IBC + DCIS. In BRCA1 and BRCA2 mutation carriers with IBC + DCIS, there was a significant correlation in ER, PR, and HER3 expression between the DCIS and IBC components. Most BRCA1-associated DCIS did not express ER, PR or HER2, while most BRCA2-associated DCIS did express ER and PR. BRCA1− as well as BRCA2-associated DCIS had expression of HER3 and C-MET. Conclusions The majority of BRCA-associated tumors had DCIS present. Concordance of DCIS and IBC phenotypes was high, arguing for the existence of a DCIS-associated premalignant pathway. Oncodrivers HER3 and C-MET were expressed in the DCIS of mutation carriers, suggesting an opportunity for prevention strategies.